Lukisan Cahaya Photobooth Enterprise / Mohammad Hafizee Md Hashim - Md Hashim, Mohammad Hafizee (2018)
First of all, Lukisan Cahaya Photobooth Enterprise is a co-own business. This business consists three (3) employees that will help in the long run regarding the operation and management of the business. The business organization is the backbone of the company itself because the way how we performed our tasks and assignment will bring the highest level of success. The main services that Lukisan Cahaya Photobooth provided is the photography and videography photo booth. While we also have photo album and guest book which is customized based on the customers, with variety of designs and colors to satisfy customer's needs. Our company is located in Bangi, Selangor. There are lots of packages to be offered to the customers and they can simply come in to our office for any consultation or booking.